The Meaning of Musicing in the Post-traumatic Growth of Individuals With Adventitious Visual Impairment: Applying the Life History Method by Mandelbaum - Park, Hye Young (Frontiers in Psychology, 2021)
This study investigated individuals with adventitious visual impairment (AVI) acquired during adulthood through a traumatic event, for an in-depth and contextual understanding of the factors and processes that led to positive changes in their post-traumatic growth. The life history method was applied on 15 individuals with AVI (seven males and eight females) through in-depth interviews about their life. The study’s analytical framework involved three domains: dimensions, turnings, and adaptations of life, as proposed by Mandelbaum. The results revealed the following key factors: of the dimensions of life—family, rehabilitation center, and music groups; of turnings of life—positive change through awareness and tolerance of impairments, new challenge posed by rehabilitation training, and finding inner resources through music; and of adaptations of life—accepting one’s life in a harsh social environment, actively establishing relationships with others as an individual with visual impairment, and re-finding meaning of life through musicing. This study contributes by revealing the role of each of the above-mentioned factors and identifying their correlations. The results suggest that musicing may help individuals with AVI develop empathy and engage in social communication through active self-disclosure.